Ambivalence in the provision of intergenerational care to older Australians and neighbourhood watch (short stories) - Gillieatt, Sue Jane (Curtin University, 2012)
This thesis examines ambivalence in the provision of intergenerational care to older Australians through analysing disciplinary and discursive literatures, reviewing fiction and memoir and writing an anthology of short stories about caring for older people. This enables a unique and complementary dialogue between two knowledges—one derived from official knowledge or institutional discourse about care and caring, the other from unofficial knowledge derived from fiction and memoir—to probe ambivalence more deeply.